How have secondary school students experienced digital work schedules? - Magyar Ágnes (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. The short- and long-term effects of the SARS-CoV-2 (Covid-19) coronavirus are the subject of numerous studies today. It is unlikely that we can think of a discipline that does not mention the role of Covid-19 in the trends observed over the last two and a half years, either as a focus of study or tangentially. The fields of pedagogy, education and training are the segments where these effects have been radical. The digitalisation of education, which will be a forced outcome for the first time in Spring 2020 and for the second time for most of the 2020-21 school year, will continue to provide a research topic for stakeholders during the periods concerned and beyond.
Hogyan élték meg a középiskolások a digitális munkarendben zajló oktatást?
Keywords: COVID-19; secondary school; motivation